Bog Bodies. Issue 6 (June 2015) - Lynnerup, Niels
ABSTRACT In northern Europe during the Iron Age, many corpses were deposited in bogs. The cold, wet and anaerobic environment leads in many cases to the preservation of soft tissues, so that the bodies, when found and excavated several thousand years later, are remarkably intact. Since the 19th century the bog bodies have been studied using medical and natural scientific methods, and recently many bog bodies have been re‐examined using especially modern, medical imaging techniques. Because of the preservation of soft tissue, especially the skin, it has been possible to determine lesions and trauma. Conversely, the preservation of bones is less good, as the mineral component has been leached out by the acidic bog. Together with water‐logging of collagenous tissue, this means that if the bog body is simply left to dry out when found, as was the case pre‐19th century, the bones may literally warp and shrink, leading to potential pitfalls in paleopathological diagnostics. Bog bodies have in several instances been crucial in determining the last meal, as gut contents may be preserved, and thus augment our knowledge on pre‐historic diet by adding to, for example, stable isotope analyses. This article presents an overview of our knowledge about the taphomic processes as well as the methods used in bog body research. Anat Rec, 298:1007–1012, 2015. © 2015 Wiley Periodicals, Inc.